DISTRIBUTION OF LUTJANIDAE AND SCIAENIDAE (PISCES) IN THE INDIAN OCEAN - Druzhinin, A D (Indian Journal of Fisheries, 2011)
Data on the distribution of 12 genera and 63 species of Lutjanidae, and 15 genera and 45 species of Sciaenidae in the Indian Ocean are described. The peculiarities of the distribution of these two families are discussed